Elastic and Optical Properties of $CeO_2$ via First-Principles Calculations (Journal of Atomic and Molecular Sciences, 2010)
The elastic and optical properties of the cubic $CeO_2$ and its behavior under pressure are investigated by using the local density approximation (LDA). The computational results are found in good agreement with the available experimental data and other theoretical results. The optical properties including dielectric function, absorption, reflectivity and refractive index are calculated and analyzed. It is found that $CeO_2$ is transparent from the partially ultra-violet to the visible light area and the transparence is hardly affected by the pressure. Furthermore, the curve of optical spectrum shifts to high energy area (blue shift) with increasing pressure.